Basel III and Bank-Lending : Evidence from the United States and Europe - Ben Naceur, Sami (IMF Working Papers; Working Paper ;, 2017)
Using data on commercial banks in the United States and Europe, this paper analyses the impact of the new Basel III capital and liquidity regulation on bank-lending following the 2008 financial crisis. We find that U.S. banks reinforce their risk absorption capacities when expanding their credit activities. Capital ratios have significant, negative impacts on bank-retail-and-other-lending-growth for large European banks in the context of deleveraging and the 'credit crunch' in Europe over the post-2008 financial crisis period. Additionally, liquidity indicators have positive but perverse effects on bank-lending-growth, which supports the need to consider heterogeneous banks' characteristics and behaviors when implementing new regulatory policies.